2014
DOI: 10.1259/bjr.20140090
|View full text |Cite
|
Sign up to set email alerts
|

Radiographers' professional knowledge regarding parameters and safety issues in plain radiography: a questionnaire survey

Abstract: Objective: To review the knowledge of radiographers and examine the possible sociodemographic and situational contributors to this knowledge. Methods: A questionnaire survey was devised and distributed to a cohort of 120 radiographers. Each questionnaire contained two sections. In the first section, background data, including sex, age, highest academic level, grade point average (GPA), length of time from graduation, work experience as a radiographer and the status of previous refresher course(s), were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This was in line with Farajollhi et al and Andersson et al who found an association between level of knowledge, academic qualifications, and years of experience. 13,14 However, this was in contrast to Alsharif et al who found that levels of radiographers' experience and qualifications did not significantly influence the level of radiographers' knowledge. 15 The mirror image artefact appears as a duplicated image, equidistant from the reflective interface but deeper to it.…”
Section: Discussionmentioning
confidence: 66%
“…This was in line with Farajollhi et al and Andersson et al who found an association between level of knowledge, academic qualifications, and years of experience. 13,14 However, this was in contrast to Alsharif et al who found that levels of radiographers' experience and qualifications did not significantly influence the level of radiographers' knowledge. 15 The mirror image artefact appears as a duplicated image, equidistant from the reflective interface but deeper to it.…”
Section: Discussionmentioning
confidence: 66%
“…Combined practical and theoretical knowledge leads to better outcomes in the teaching field and empowers more self-confidence of those working in the profession. Such a combined approach to teaching would enable learners to work more competently and be prepared to take responsibility in their future careers [40]. Knowledgeable and well-trained students play an important role in the creation of a positive radiation safety culture.…”
Section: Discussionmentioning
confidence: 99%
“…Since each Pre-and Post-image pairs were taken with different image acquisition parameters and post-processing algorithms [14], these effects cannot be normalized from rescaling the image in the image processing step. As a result, the obtained ROI values need to be adjusted to compare.…”
Section: Discussionmentioning
confidence: 99%